Asymmetric Flow Field-Flow Fractionation: Current Status, Possibilities, Analytical Limitations and Future Trends - Podzimek, Štěpán; Johann, Christoph (Springer, 2021)
The development and applications of asymmetric flow field-flow fractionation (AF4) are outlined in comparison with the older and better-known size exclusion chromatography. Recent advances in AF4 instrumentation and predictions for further progress of the technique are given.
Frakcionace tokem v asymetrickém tokovém poli: Současný stav, možnosti, analytická omezení a budoucí trendy
Keywords: asymmetric flow field-flow fractionation; size exclusion chromatography; frakcionace tokem v asymetrickém tokovém poli; rozměrově vylučovací chromatografie